Correction: Palladium(ii) complexes with chelating N-phosphanyl acyclic diaminocarbenes: synthesis, characterization and catalytic performance in Suzuki couplings. Issue 4 (24th December 2015) - Marchenko, Anatoliy; Koidan, Georgyi; Hurieva, Anastasiya; Vlasenko, Yurii; Kostyuk, Aleksandr; Biffis, Andrea
Abstract : Correction for 'Palladium(ii ) complexes with chelating N -phosphanyl acyclic diaminocarbenes: synthesis, characterization and catalytic performance in Suzuki couplings' by Anatoliy Marchenko et al., Dalton Trans., 2016, DOI: 10.1039/c5dt02250a.